Consumer Ruthlessness and Mortgage Default during the 2007 to 2009 Housing Bust - BHUTTA, NEIL; DOKKO, JANE; SHAN, HUI (Journal of Finance, 2017)
ABSTRACT From 2007 to 2009 U.S. house prices plunged and mortgage defaults surged. While ostensibly consistent with widespread “ruthless default,” analysis of detailed mortgage and house price data indicates that borrowers do not walk away until they are deeply underwater—far deeper than traditional models predict. The evidence suggests that lender recourse is not the major driver of this result. We argue that emotional and behavioral factors play an important role in decisions to continue paying. Borrower reluctance to walk away implies that the moral hazard cost of default as a form of social insurance may be lower than suspected.